2019
DOI: 10.3346/jkms.2019.34.e288
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Services for Autism Spectrum Disorder in Massachusetts with Those in Seoul

Abstract: BackgroundThis article intended to identify and describe areas in need of services and interventions for individuals with autism spectrum disorder (ASD) and their families in Seoul, Korea.MethodsA descriptive comparison was made between available services and interventions in Seoul, Korea and Massachusetts, USA. Relevant information was obtained through sending phone/email inquiries to the governments and organizations, visiting their official websites, and searching for published articles or reports.ResultsIn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…However, children with autism and DD have limited access to public services, and ABA services that are overseen by board certified behavior analysts (BCBAs) are not covered by the health care system (Hong et al, 2020). The availability of ABA services is limited in quantity, as evidenced by having only 56 BCBAs registered to practice in Seoul, which is the capital city of South Korea with around 30,000 children with DD (Behavior Analyst Certification Board, 2020; Kim et al, 2019).…”
Section: Parents In South Koreamentioning
confidence: 99%
See 1 more Smart Citation
“…However, children with autism and DD have limited access to public services, and ABA services that are overseen by board certified behavior analysts (BCBAs) are not covered by the health care system (Hong et al, 2020). The availability of ABA services is limited in quantity, as evidenced by having only 56 BCBAs registered to practice in Seoul, which is the capital city of South Korea with around 30,000 children with DD (Behavior Analyst Certification Board, 2020; Kim et al, 2019).…”
Section: Parents In South Koreamentioning
confidence: 99%
“…South Korea is a high-income country with a universal health care system (Kim et al, 2019). However, children with autism and DD have limited access to public services, and ABA services that are overseen by board certified behavior analysts (BCBAs) are not covered by the health care system (Hong et al, 2020).…”
Section: Parents In South Koreamentioning
confidence: 99%
“…Furthermore, because Korea has fewer schools and facilities (i.e. personal care, social training, and skilled nursing facility) for children and adolescents with ASD than other countries, those with ASD have fewer social contacts than even before the COVID-19 pandemic ( Kim et al, 2019 ; Lee & Yun, 2019 ). In addition, it has been reported that most adults with ASD were not fully vaccinated, therefore, the COVID-19 prevalence is higher among those with ASD ( Lunsky et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a risk that the number of people with ASD is underestimated in the disability registry due to issues such as stigma. 1 4 32 The National Health Insurance claims data provide information on everyone in the Republic of Korea who received care for ASD. However, it is possible that the actual social burden due to ASD may be overestimated.…”
Section: Discussionmentioning
confidence: 99%